Combination of Synthetic Long Peptides and XCL1 Fusion Proteins Results in Superior Tumor Control - Botelho, Natalia K.; Tschumi, Benjamin O.; Hubbell, Jeffrey A.; Swartz, Melody A.; Donda, Alena; Romero, Pedro (Frontiers in Immunology, 2019)
Cross-presenting Xcr1+CD8 DCs are attractive APCs to target for therapeutic cancer vaccines, as they are able to take up and process antigen from dying tumor cells for their MHCI-restricted presentation to CD8 T cells. To this aim, we developed fusion proteins made of the Xcr1 ligand Xcl1 fused to an OVA synthetic long peptide (SLP) and IgG1 Fc fragment. We demonstrated the specific binding and uptake of the Xcl1 fusion proteins by Xcr1+ DCs. Most importantly, their potent adjuvant effect on the H-2Kb/OVA specific T cell response was associated with a sustained tumor control even against the poorly immunogenic B16-OVA melanoma tumor. The increased tumor protection correlated with higher tumor infiltration of antigen-specific CD8+ T cells, increased IFNγ production and degranulation potential. Altogether, these results demonstrate that therapeutic cancer vaccines may be greatly improved by the combination of SLP antigen and Xcl1 fusion proteins.